Additive manufacturing, the path to industrialisation at CSIRO. Issue 5 (20th October 2021) - Wilson, Robert; Yan, Shiqin; Doblin, Christian; Alam, Nazmul; East, Daniel; Liang, Daniel; Vargas-Uscategui, Alejandro; Urban, Andrew; Regos, Emma; Zahiri, Saden; King, Peter C.; Gulizia, Stefan; et al.
ABSTRACT: CSIRO has extensive experience and track record in turning powders into products. Through the CSIRO Lab 22 and associations, the teams in CSIRO are tailoring metal powders to processes, repurposing waste for additive manufacturing (AM) processes and generating unique materials, products and processes for Australia. The laboratory also houses Australia's own metal printer from Aurora Labs that can operate in both direct laser melting (DLM) and laser powder bed fusion (LPBF) modes. This paper discusses capability and case study examples, with some scientific detail, as we work to mainstream and industrialise AM.